Isolation and Optimization of Culture Conditions of Thraustochytrium kinnei for Biomass Production, Nanoparticle Synthesis, Antioxidant and Antimicrobial Activities - Kaliyamoorthy Kalidasan; Nabikhan Asmathunisha; Venugopal Gomathi; Laurent Dufossé; Kandasamy Kathiresan (Journal of Marine Science and Engineering, 2021)
This work deals with the identification of a predominant thraustochytrid strain, the optimization of culture conditions, the synthesis of nanoparticles, and the evaluation of antioxidant and antimicrobial activities in biomass extracts and nanoparticles. Thraustochytrium kinnei was identified as a predominant strain from decomposing mangrove leaves, and its culture conditions were optimized for maximum biomass production of 13.53 g·L−1, with total lipids of 41.33% and DHA of 39.16% of total fatty acids. Furthermore, the strain was shown to synthesize gold and silver nanoparticles in the size ranges of 10–85 nm and 5–90 nm, respectively. Silver nanoparticles exhibited higher total antioxidant and DPPH activities than gold nanoparticles and methanol extract of the strain. The silver nanoparticles showed higher antimicrobial activity than gold nanoparticles and petroleum ether extract of the strain. Thus, Thraustochytrium kinnei is proven to be promising for synthesis of silver nanoparticles with high antioxidant and antimicrobial activity.